A thoracoabdominal approach for gastrobronchial fistula repair post complicated laparoscopic sleeve gastrectomy - Alshammari, Abdullah (Int J Surg Case Rep, 2018)
INTRODUCTION: There has been a recent surge in bariatric surgery. Consequently, identification of new complications is imminent. Gastrobronchial fistula is one of the newly identified severe complications. The medical community is yet to come up with a consensus on management, which is further complicated by the lack of literature on par with its rarity. Therefore, we aim to contribute to a better understanding and add to the managerial approach. PRESENTATION OF CASE: We report a case of a 36-year-old female. Post-operative stenting and esophageal dilation was performed. 15 months post LSG patient presented with productive cough with green sputum, food particle and left sided chest pain. Endoscopic clip placement was attempted with no avail. The surgical approach involved posterolateral thoracotomy for left lower lobe resection with debridement of eroded diaphragm. The abdominal cavity was accessed via a medial diaphragmatic incision. The situation necessitated a splenectomy. Singular repair, with omental patch was performed. The jejunum was brought to the site of the fistula and the opening was covered with clean serosa. DISCUSSION: The management of gastrobronchial fistulas involves a comprehensive clinical evaluation. In the absence of red flags, an initial conservative management should be undertaken. When all else fail, surgery is the only route towards a permanent and definitive treatment. CONCLUSION: The need for further research and consensus is of utmost importance to guide future surgeons and to increase awareness among the medical community, due to its presentation under the facade of common symptoms.